Beclin‐1 Is Required for RANKL‐Induced Osteoclast Differentiation. Issue 12 (December 2014) - Chung, Yeon‐Ho; Jang, Youngsaeng; Choi, Bongkun; Song, Da‐Hyun; Lee, Eun‐Jin; Kim, Sang‐Min; Song, Youngsup; Kang, Sang‐Wook; Yoon, Seung‐Yong; Chang, Eun‐Ju
<x xml:space="preserve">Abstract</x> Beclin‐1 plays a critical role in autophagy; however, it also contributes to other biological processes in a non‐autophagic manner. Although studies have examined the non‐autophagic role of autophagy proteins in the secretory function of osteoclasts (OC), the role of Beclin‐1 is unclear. Here, we examined the role of Beclin‐1 in OC differentiation, and found that mouse bone marrow macrophages (BMMs) showed increased expression of Beclin‐1 upon RANKL stimulation in a p38‐ and NF‐kappa B‐dependent manner. During OC differentiation, Beclin‐1 localized to the mitochondria, where it was involved in the production of mitochondrial intracellular reactive oxygen species. Knockdown of Beclin‐1 in RANKL‐primed BMMs led to a significant reduction in RANKL‐dependent osteoclastogenesis, which was accompanied by reduced NFATc1 induction. Furthermore, knockdown of Beclin‐1 inhibited RANKL‐mediated activation of JNK and p38, both of which act downstream of reactive oxygen species, resulting in the suppression of NFATc1 induction. Finally, overexpression of constitutively active NFATc1 rescued the phenotype induced by Beclin‐1 knockdown, indicating that Beclin‐1 mediates RANKL‐induced osteoclastogenesis by regulating NFATc1 expression. These findings show that Beclin‐1 plays a non‐autophagic role in RANKL‐induced osteoclastogenesis by inducing the production of reactive oxygen species and NFATc1. J. Cell. Physiol. 229: 1963–1971, 2014. © 2014 Wiley Periodicals, Inc.